Characterization of Chicken Feather Waste in Me Linh, Hanoi - Thi Hoang Oanh, Le; Thu Trang, Dang; Thi Minh Phuong, Dang; Van Quang, Pham; Minh Loan, Luu; Huu Huan, Nguyen; Hong, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2DO - 10.25073/2588-1094/vnuees.5279, 2025)
Chicken feather waste, a byproduct of the slaughtering process, may pollute the environment and pose a risk to human health. However, it is a potential source of organic nitrogen for agricultural application, such as animal feed and fertilizers. In Vietnam, Me Linh district, a large flower, vegetable and fruit growing area, is also among the top of fertilizer use in Hanoi city, where the demand for organic fertilizer is high. This study was carried out to evaluate the quality of the chicken feather waste in Me Linh district for further agricultural application. Here we focused on the chicken feather waste distribution, generation rate, bulk density, pH, and extractables. The measured elemental composition of chicken feather waste was similar to previous studies.  They are rich in nitrogen (TN ~ 12%), have high sulfur content (TS > 2%), and do not contain heavy metals, which are strictly regulated in QCVN 01-189/2019-BNNPTNT as for bio-organic fertilizer quality standards.